ANALYSIS OF TRADERS' WASTE MANAGEMENT SYSTEM ON THE FLY POPULATION INDEX - Faisal Fahri; Eka Joni Yansyah; Yulis Marita; Fera Meliyanti (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Flies are disease vectors that can cause health problems, especially in environments with poor sanitation. Inadequate waste management in traditional markets can increase fly populations, potentially leading to disease outbreaks. This study aims to analyze the relationship between waste management systems (storage, collection, and transportation) and the fly population index in Pasar Baru Baturaja, Ogan Komering Ulu (OKU) Regency. This study used an observational analytic design with a cross-sectional approach. The study population consisted of 150 traders in Pasar Baru Baturaja, with a sample of 60 respondents selected using Stratified Random Sampling. Data were collected through interviews with questionnaires and analyzed using the Chi-Square test. The results showed that 80% of respondents had a high fly population index. 86.7% of respondents did not meet the requirements for waste storage, 73.3% for waste collection, and 70% for waste transportation. There was a significant relationship between waste storage (p-value = 0.004), collection (p-value = 0.007), and transportation (p-value = 0.009) with the fly population index. Poor waste management systems, particularly in storage, collection, and transportation, contribute to the high fly population in Pasar Baru Baturaja. Improvements in waste management infrastructure, such as providing separate, watertight, and covered waste bins, are needed. Additionally, regular monitoring and socialization by market management are necessary to increase traders' awareness of maintaining environmental cleanliness.